Cingulin b Is Required for Zebrafish Lateral Line Development Through Regulation of Mitogen-Activated Protein Kinase and Cellular Senescence Signaling Pathways - Lu, Yitong; Tang, Dongmei; Zheng, Zhiwei; Wang, Xin; Zuo, Na; Yan, Renchun; Wu, Cheng; Ma, Jun; Wang, Chuanxi; Xu, Hongfei; He, Yingzi; Liu, Dong; et al. (Frontiers in Molecular Neuroscience, 2022)
Cingulin, a cytoplasmic element of tight junctions (TJs), is involved in maintenance of the integrity of epithelial and endothelial cells. However, the role of cingulin in the development of auditory organs remains unclear. Zebrafish is popular as a model organism for hearing research. Using the whole mount in situ hybridization (WISH) experiment, we detected the expression of cingulin b in the posterior lateral line system (PLLs) of zebrafish. We traced the early development progress of zebrafish PLLs from 36 hpf to 72 hpf, and found that inhibition of cingulin b by target morpholinos resulted in severe developmental obstruction, including decreased number of neuromasts, reduced proliferative cells in the primordium, and repressed hair cell differentiation in the neuromasts. To examine the potential mechanism of cingulin b in the development of zebrafish PLL neuromasts, we performed RNA-seq analysis to compare the differently expressed genes (DEGs) between cingulin b knockdown samples and the controls. The KEGG enrichment analysis revealed that MAPK signaling pathway and cellular senescence were the key pathways with most DEGs in cingulin b-MO morphants compared to the Control-MO embryos. Furthermore, quantitative RT-PCR analysis confirmed the findings by RNA-seq that the transcript levels of cell cycle negative regulators such as tp53 and cdkn1a, were remarkably upregulated after inhibition of cingulin b. Our results therefore indicated an important role of cingulin b in the development of auditory organs, and MAPK signaling pathway was inhibited while cellular senescence pathway was activated after downregulation of cingulin b. We bring forwards new insights of cingulin by exploring its function in auditory system.